(untitled) (Al-Qamar, 2021)
Naturally, man is ever anxious to know its future. Semitic religions provide evidences regarding the governance of a justice person near the end of this world close to the end of time. Islam, being the youngest Dīn, also provides evidences through its divine book, Al-Quran, and sayings of the Last Prophet Muhammad(ﷺ)۔ Muslim scholars put a considerable focus on Quranic and Hadith teaching in the perspective of Imam Mehdi, the last justice ruler. A non-Muslim minority in Pakistan made explanations of these Hadiths according to their fabricated proclivities to develop wrong inclinations among Muslims. Pīr Meher Alī Shāh did a remarkable and government record work on the Hadith regarding Imam Mehdi and rebuttal of wrong interpretations but academic research on his work is rare so there is need to elaborate the work for future educational and scholastic benefits. The article provides a critical explanation on views of Pīr Syed Meher Alī Shah regarding Hadiths about Imām Mehdī.